2011
DOI: 10.3109/00048674.2011.561479
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Patients' Perceptions of Schizophrenia Between Māori and New Zealand Europeans

Abstract: Illness perceptions provide a framework to assess patients' beliefs about their mental illness. Differences between Māori and New Zealand European patients' beliefs about their mental illness may be related to traditional Māori beliefs about mental illness. Knowledge of differences in illness perceptions provides an opportunity to design effective clinical interventions for both Māori and New Zealand Europeans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Our results are also consistent with the results of three recent studies on the importance of psychosocial causal beliefs and their link with better clinical outcomes (Sanders et al 2011; Lüllmann et al 2011; Freeman et al 2012). Our study suggests that integrating psychosocial and biological aspects within a causal model in psychosocial intervention programs may be more efficacious than focusing only on the biological model, and basing treatment only on prescribing of antipsychotic drugs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are also consistent with the results of three recent studies on the importance of psychosocial causal beliefs and their link with better clinical outcomes (Sanders et al 2011; Lüllmann et al 2011; Freeman et al 2012). Our study suggests that integrating psychosocial and biological aspects within a causal model in psychosocial intervention programs may be more efficacious than focusing only on the biological model, and basing treatment only on prescribing of antipsychotic drugs.…”
Section: Discussionsupporting
confidence: 92%
“…However, medications alone are not sufficient for recovery in schizophrenia, and psychosocial treatments are a necessary complement (Kern et al, 2009). Three recent studies suggested that a psychosocial causal model could be relevant for treatment success by promoting non-pharmacological treatment (Sanders, et al, 2011; Lüllmann et al, 2011; Freeman et al, 2012). Causal beliefs may also act in divergent ways across the spectrum of treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cameron Lacey 1,2,3 To the Editor We read with interest the paper by Sanders and colleagues (Sanders et al, 2011) investigating the perceptions of schizophrenia among Maori and non-Maori. It is pleasing to see research that attempts to give voice to the experience and views of tangata whaiora regarding their illnesses and future.…”
Section: Re: Sanders Et Al (2011) Differences In Patients' Perceptiomentioning
confidence: 87%
“…Research on Māori and Pakeha (European) people being treated for schizophrenia within clinical services did not demonstrate a difference in attitude towards medication (Sanders et al, 2011). Being aware of the importance of Māori culture should not come with assumptions that Māori will be necessarily opposed to or not interested in information about schizophrenia as a medical condition and the effective treatments available.…”
Section: Schizophrenia In Māorimentioning
confidence: 99%